A Case of Lyme Carditis Presenting with Atrial Fibrillation. (2nd September 2018) - Kennel, Peter J.; Parasram, Melvin; Lu, Daniel; Zisa, Diane; Chung, Samuel; Freedman, Samuel; Knorr, Katherine; Donahoe, Timothy; Markowitz, Steven M.; Halazun, Hadi
Abstract : We report a case of a 20-year-old man who presented to our institution with a new arrhythmia on a routine EKG. Serial EKG tracings revealed various abnormal rhythms such as episodes of atrial fibrillation, profound first degree AV block, and type I second degree AV block. He was found to have positive serologies for Borrelia burgdorferi . After initiation of antibiotic therapy, the atrial arrhythmias and AV block resolved. Here, we present a case of Lyme carditis presenting with atrial fibrillation, a highly unusual presentation of Lyme carditis.